Transfer of htlv-1 p8 and gag to target t-cells depends on vasp, a novel interaction partner of p8 - Donhauser, Norbert; Socher, Eileen; Millen, Sebastian; Heym, Stefanie; Sticht, Heinrich; Thoma-Kreß, Andrea (PLoS Pathogens, 2020)
The Human T-cell leukemia virus type 1 (HTLV-1) orf I-encoded accessory protein p8 is cleaved from its precursor p12, and both proteins contribute to viral persistence. p8 induces cellular protrusions, which are thought to facilitate transfer of p8 to target cells and virus transmission. Host factors interacting with p8 and mediating p8 transfer are unknown. Here, we report that vasodilator-stimulated phosphoprotein (VASP), which promotes actin filament elongation, is a novel interaction partner of p8 and important for p8 and HTLV-1 Gag cell-to-cell transfer. VASP contains an Ena/VASP homology 1 (EVH1) domain that targets the protein to focal adhesions. Bioinformatics identified a short stretch in p8 (amino acids (aa) 24-45) which may mediate interactions with the EVH1 domain of VASP. Co-immunoprecipitations confirmed interactions of VASP:p8 in 293T, Jurkat and HTLV-1-infected MT-2 cells. Co-precipitation of VASP:p8 could be significantly blocked by peptides mimicking aa 26-37 of p8. Mutational studies revealed that the EVH1-domain of VASP is necessary, but not sufficient for the interaction with p8. Further, deletion of the VASP G- and F-actin binding domains significantly diminished co-precipitation of p8. Imaging identified areas of partial co-localization of VASP with p8 at the plasma membrane and in protrusive structures, which was confirmed by proximity ligation assays. Co-culture experiments revealed that p8 is transferred between Jurkat T-cells via VASP-containing conduits. Imaging and flow cytometry revealed that repression of both endogenous and overexpressed VASP by RNA interference or by CRISPR/Cas9 reduced p8 transfer to the cell surface and to target Jurkat T-cells. Stable repression of VASP by RNA interference in chronically infected MT-2 cells impaired both p8 and HTLV-1 Gag transfer to target Jurkat T-cells, while virus release was unaffected. Thus, we identified VASP as a novel interaction partner of p8, which is important for transfer of HTLV-1 p8 and Gag to target T-cells.
CRIS-Team Scopus Importer:2020-10-16